Penggunaan Digital Storytelling Untuk Meningkatkan Keterampilan Berbicara Siswa Sekolah Dasar - Moh Asyadi; Geraldy Jeremia Taere; Aura Ramadani Toha; Wahyu Pratama (JURNAL DIKDAS, 2025)
Technological advances in education have brought various innovations, one of which is digital Storytelling. Digital Storytelling is a Storytelling method that utilizes digital technology, such as images, video, audio, animation, and text, to create an interactive and engaging narrative experience. This study aims to examine the effectiveness of using digital Storytelling in improving the speaking skills of elementary school students. In this study, the method used by researchers is the Systematic literature review (SLR) method which uses a qualitative approach called meta-synthesis. This research data collection uses the theoretical basis of relevant articles, namely Google Scholar, Elicit AI and Publish or Perish. The articles collected by researchers are articles published in the interval 2014-2024 which are the source of research. Based on the results of the literature study conducted, the use of digital Storytelling has been proven to be effective in improving the speaking skills of students in elementary schools. Students who participate in the activity can improve their understanding of speaking skills by learning narrative learning, can ask questions and share views which also strengthens their emotional intelligence and cooperation.